2021 - IFAD-EU/CCAFS CSA Monitoring: Basona Werana Climate-Smart Village (Ethiopia) - Bonilla-Findji, Osana; Eitzinger, Anton; Abera, Wuletawu; Tamene, Lulseged D.; Recha, John W.M.; Ambaw, Gebermedihin; Nigussie, Abebe; Tesfaye, Abonesh (2021)
This monitoring framework developed by CCAFS is meant to be deployed annually across the global network of Climate-Smart Villages to gather field-based evidence by tracking the progress on: adoption of CSA practices and technologies, as well as access to climate information services and their related impacts at household level and farm level